2010
DOI: 10.1111/j.1439-0396.2010.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Brain and hypophyseal acetylcholinesterase activity of pubertal boars fed dietary fumonisin B1

Abstract: The effects of dietary fumonisin B(1) (FB(1)) on regional brain and hypophyseal activities of AChE (EC 3117), the enzyme which catalyses the hydrolysis of acetylcholine, were studied using 24 male Large White weanling pigs divided into four groups. Each group received one of the four diets containing 0.2, 5.0, 10.0 and 15.0 mg FB(1)/kg in a 6-month feeding trial. All animals were slaughtered at the end of the feeding trial; the brains and the hypophyses obtained were carefully dissected out. Significant (p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…(). This study demonstrated that feed contaminated with FB 1 ≥ 5 mg/kg feed for a 6‐month period decreased in a dose dependent manner the release AChE and SAChE activity from some brain regions (Gbore, ).…”
Section: Assessmentmentioning
confidence: 77%
“…(). This study demonstrated that feed contaminated with FB 1 ≥ 5 mg/kg feed for a 6‐month period decreased in a dose dependent manner the release AChE and SAChE activity from some brain regions (Gbore, ).…”
Section: Assessmentmentioning
confidence: 77%
“…Kenk et al (305) demonstrated via positron emission tomography imaging of cAMP, a strong region-specific signal in the brain, as well as an impaired cAMP-mediated signalling in obese pigs, giving some insight into pathological progression with potential for directing therapy in humans. Gbore (309) demonstrated that the acetylcholinesterase activity in the hypophyses, hypothalamus and amygdala decreased with increased mycotoxin concentrations in the diet. The decreased feed intake and increased aggressive behaviour observed in subjects contaminated with mycotoxins might be related to anomalies in brain monoamines, including dopamine and serotonin.…”
Section: Differences Between Pigs and Humans Or Pig Studies With No mentioning
confidence: 99%
“…The decreased feed intake and increased aggressive behaviour observed in subjects contaminated with mycotoxins might be related to anomalies in brain monoamines, including dopamine and serotonin. Gbore ( 309 ) demonstrated that the acetylcholinesterase activity in the hypophyses, hypothalamus and amygdala decreased with increased mycotoxin concentrations in the diet. These results are important to identify the risk associated with mycotoxin contamination and possible therapeutic interventions in humans.…”
Section: The Relationship Between Nutrition and The Brain In The Pigmentioning
confidence: 99%
“…In the other hand, the liver and kidney were also damaged even; they are speci c hosts for FB1 accumulation (Hou et al, 2021;Demirel et al, 2015;Rumora et al, 2007). In the brain, FB1 was able to generate oxidative stress markers (Baldissera et al, 2020), neurochemistry toxicity (Gbore, 2010), facilitated seizures, as well as brain hyperexcitability (Poersh et al, 2015). Several studies reported also that FB1 induced immunotoxicity (Abbès et al, 2016), apoptosis (Zhang et al, 2018;Kim et al, 2018) and genotoxicity (Müller et al, 2012;Pinhão et al, 2020).…”
Section: Introductionmentioning
confidence: 99%